Comparative analysis of various VO2max development sessions - Hanon, C.; Lehenaff, D.; Gajer, B.; Vollmer, J. C. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Since the 1950s and the "interval-training" made popular by Emil Zatopek, an emblematic figure of this method, intermittent training, by opposition to continuous effort, has kept on expanding. Various purposes can be correlated to such a development, but the so-called intermittent training is most commonly associated to the development of athletes' aerobic potential. In this frame, several authors have proved that intermittent effort was more efficient than continuous effort. Indeed, Gorostiaga et al. (1991) demonstrated that the VO2max increase was significantly higher after 24 sessions of intermittent training (30s~30s at 100% of VO2max) than after a continuous effort at 50% of VO2max. In the same way, Billat et al. (2000), comparing two continuous and discontinuous sessions performed at the same mean strength, revealed that the discontinuous session enabled to make use of VO2max three times as longer as the continuous one. The efficiency of intermittent effort does not seem to be questionable. However, the multiple forms deriving from this training basis can vary depending on the sequence intensity or duration and the recovery time length. The experimental work proposed aims at characterising the sessions in relation to certain modalities of the sequence duration and intensity. We intentionally oriented our study towards the trainer's perspective, in order to compare: one session of VO2max development on slopes, and two flat race sessions. One of these two sessions repeats the duration of the slope training effort (i.e. 1 min30), the other corresponds to a "classic" session of short intermittent effort (30s~30s).